Opportunistic Backscatter Communication Protocol Underlying Energy Harvesting IoT Networks - Arshad Iqbal; Tae-Jin Lee (IEEE Access, 2023)
Traditional WiFi devices, wireless energy harvesting devices, sensor-driven smart gadgets, and backscatter communication tags can all be part of a heterogeneous wireless network. In the Internet of Things (IoT), the recently developed backscatter communication technology allows for battery-free communication. However, when wireless energy transmissions coexist alongside wireless data transmissions, collisions and interference become more frequent. In this paper, we present a heterogeneous wireless energy harvesting IoT network using an Opportunistic Backscatter communication Medium access control (OBM) protocol. It allows the backscatter tags to communicate with the reader in an energy harvesting IoT network in a smooth manner. For contention and communication, the backscatter tags employ the radio frequency (RF) signals provided by the hybrid access point (HAP) to the energy-strapped wireless nodes. When the devices request the HAP for wireless energy harvesting, the reader stimulates the tags for contention and communication. To access the channel with fewer collisions, wireless devices and backscatter tags utilize different contention techniques. For backscatter communications, network throughput, and energy efficiency, we identified the transmission probability of devices and tags, energy harvesting, and data transmission probability of nodes. When compared to traditional methods, the proposed protocol improves network throughput performance and energy efficiency.